Synthesis of A Novel Polycarboxylate Superplasticizer with High Performance - Zhou1, Keli; Liu1, Jin; Li1, Zhen (Asian Journal of Chemistry, 2011)
The novel polycarboxylate superplasticizers (NPCS) were prepared by copolymerizing of novel maleic anhydride citric acid ester (MACA), methoxyl polyethylene glycol ether methyl acrylate (MPEGMAA), acrylic acid (AA), a-methylacrylic acid (MAA), sodium alkyl sulfonate (SAS). The structure and properties of novel polycarboxylate superplasticizers were characterized by FTIR, intrinsic viscosity and surface tension. Moreover, the application properties of the fluidity, zeta potential and drying shrinkage of adding novel polycarboxylate superplasticizers into cement paste were also investigated. The results showed that the fluidity of cement grout reached as high as 360 mm at the copolymer usage of 0.25 wt %, water-cement ratio of 0.29. No obvious loss of fluidity occurred within 2 h and the cement paste without bleeding and segregation was homogeneous. In addition, the novel polycarboxylate superplasticizer is good for reducing the drying shrinking, improving the mesoporous volume and making cement hardenite more compact by proved from N2 adsorption and desorption measurement.